Thyroid Autoimmunity and Function in Type 1 Diabetic Children and Adolescents in Armenia - Navasardyan, L.V.; Tadevosyan, A.E. (International Journal of Child Health and Nutrition, 2013)
<!-- [if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> The literature and research clearly supports an increased incidence of autoimmune thyroid disorders (mostly autoimmune thyroiditis) in type 1 diabetics as well as increased incidence of type 1 diabetes mellitus (DM) in autoimmune thyroid disease. The objective of current epidemiological screening study is to investigate thyroid autoimmunity and function in a large cohort of children and adolescents with type 1 DM in Armenia. Moreover, this screening study is done to determine the incidence of thyroid autoimmunity and hypothyroidism (including sub clinical hypothyroidism) and to give its structural analysis. The findings of current study illustrate 30.5% of hypothyroidism, including subclinical hypothyroidism, in type 1 diabetic children and adolescents. What is more important, 24.8% of type 1 diabetic children and adolescents have thyroid autoimmunity – positive antithyroid peroxidase autoantibodies (Anti-TPO), 44% from which were found to be significantly high. Any sex predominance was not found in AIT and thyroid autoimmunity in general. In type 1 diabetics with associated thyroid autoimmunity autoantibody positivity precedes thyroid ultrasound changes and predisposes to the development of further hypothyroidism without any sex predominance. The number of cases of hypothyroidism is quite high in the group of diabetics with DM duration of 5 years. It is recommended that diabetics who have no TSH elevation and thyroid ultrasound changes, but who have increased Anti-TPO, should be formed as a group of high risk for further development of thyroid disorders, although TSH elevation showed having no influence on the compensation of diabetes. We fully recommend the patients to test the TSH and anti-TPO levels once a year, particularly after puberty and with DM duration over 5 years. <span style="font-size: 10.0pt; mso-bidi-font-size: 14.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> <!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif";} --> <!--[endif] -->